Metastatic Behavior in Melanoma: Timing, Pattern, Survival, and Influencing Factors - Tas, Faruk (Hindawi Publishing Corporation, 2012)
Metastatic melanoma (MM) is a fatal disease with a rapid systemic dissemination. This study was conducted to investigate the metastatic behavior, timing, patterns, survival, and influencing factors in MM. 214 patients with MM were evaluated retrospectively. Distant metastases (82%) were the most frequent for patients initially metastatic. The median and 1-year survival rates of initially MM patients were 10 months and 41%, respectively. The median time to metastasis for patients with localized disease was 28 months. The timing of appearance of metastases varied minimally; however, times to metastases for distant organs varied greatly. For the first metastatic pathway, more than half of the primary metastases were M1A (57%). These findings were in contrast to the results compared with those with metastatic in diagnosis (P < 0.001). The median and 1-year survival rates of all patients were 12 months and 49%, respectively. Outcome was higher in M1A than visceral metastases (P < 0.001). In conclusion, the fact that over half of all recurrences/metastases occurred within 3 years urges us to concentrate follow-up in the early time periods following diagnosis. Because the clinical behavior of MM is variable, the factors for survival consisting of site and number of metastases should be emphasized.